The Key Role of Bone Function Markers in Patients with Type (II) Diabetes Mellitus - Balaky, HazharHazhar M.; Kakey, Ismail S. (Iraqi Journal of Science, 2022)
Complications associated with diabetes are a consequence of acute disturbance in glucose metabolism in a human body. The most significant complication of diabetes is bone disorders which contributes to high levels of bone disability. This study included 118 diabetic patients, 56 males, 62 females, and 60 healthy non-diabetic controls, 30 males, 30 females. The patients and controls were age matched. Circulating levels of bone function markers (osteoprotegerin, vitamin D, PTH, total calcium and inorganic phosphorus) were determined in all subject groups. The data obtained from this study showed that the serum levels of osteoprotegerin had significantly increased in both diabetic male & female in both age ranges which were 496.3±61.46 pg/mL & 335.7±29.33 pg/mL; 329.8±48.78 pg/mL & 219.9±18.72 pg/mL respectively, in comparison with its level in control matched age ranges 294.6±26.19 pg/mL & 226.8±28.07 pg/mL; 215.7±31.85 pg/mL & 171.9±14.19 pg/mL respectively. Serum calcium concentration had non-significantly increased both in the diabetic males and females in both age ranges which were 11.10±0.46 mg/dL & 11.76±0.74 mg/dL; 10.33±0.33 mg/dL & 10.28±0.48 mg/dL respectively, when compared with its level in control matched age ranges 10.46±0.34 mg/dL & 10.14±0.35 mg/dL;9.69±0.41 mg/dL & 10.08±0.45 mg/dL. Serum vitamin D, parathyroid hormone (PTH) and inorganic phosphorus concentrations had significantly decreased both in the diabetic male and female subjects in both age ranges which were 5.78±1.30 ng/mL and 2.47±0.12 ng/mL; 9.47±1.98 ng/mL, and 10.70±2.11 ng/mL; 74.78±7.42 pg/mL & 67.83±3.69 pg/mL;42.94±2.00 pg/mL & 15.51±1.98 pg/mL; 4.34±0.27 mg/dL & 4.76±0.35 mg/dL; 4.38±0.21 mg/dL; 5.12±0.44 mg/dL respectively when compared with their level in control matched age ranges 13.07±2.13 ng/mL & 15.53±3.40 ng/mL; 57.49±5.64 pg/mL & 62.61±3.71 pg/mL; 5.12±0.44 mg/dL & 5.35±0.37 mg/dL respectively. The current results suggest that circulating levels of osteoprotegerin play a crucial role in biological mechanism of type (II) diabetes, and are possible biomarkers of insulin resistance and progression of many serious health problems associated with diabetes.